Perceptions of male vs. female English L2 speaker comprehensibility - Head, Philip; Yamane, Noriko (Frontiers in Education, 2025)
Evaluation of English as an additional language (L2) speech comprehensibility in classroom and standardized test situations is important for students’ academic and career success. While previous research has found phonetic differences between male and female speech, as well as disparities in language learning ability and academic achievement, little is known about how these gender-related factors affect listener evaluations of L2 speech. This study examined responses of 201 raters from 23 first language (L1) backgrounds to the question of whether or not there are differences in male and female English L2 speaker comprehensibility. The results indicated that 66.7% perceived no difference, 27.9% judged female speakers to be easier to understand, and only 5.5% judged male speakers to be easier to understand. Written comments were coded and frequencies of codes compared in terms of rater sex and teaching experience. While overall likelihood of perceiving gender effects did not differ, the reasons given did. Male raters and teachers tended to reject gender differences on philosophical grounds, whereas students more often reported never noticing them. Among those who perceived gender differences, lower male voice pitch was seen as hindering intelligibility, while females were thought to make greater efforts at clarity and correction. Greater familiarity with female L2 speech was also cited, highlighting potential gender bias in listener judgments of comprehensibility. Based on these findings, implications and recommendations for ensuring fairness in L2 assessment are presented.